Cultural Acculturation Study of Visual Form of Facades and Spatial Organization of Glodok’s Shophouses, Jakarta Barat, Indonesia - Tiffany Tiffany; Nurhayatu Nufut Alimin (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2023)
Ethnic Chinese is ethnic that can preserve their culture from foreign influence from time to time. China has undergone several diasporas, leading to many ethnic Chinese that we can see in various countries today, including Indonesia. The Chinese immigrants then lived together in an area called ‘Chinese town’ or, in Indonesian, called ‘pecinan,’ whose shophouse (Rumah Toko) is the town’s landmark. It asks how the architecture and interior of the shophouse in Chinatown in Indonesia (one of the Dutch colonies) were shaped and how the cultural acculturation happened in this historic building. This research is trying to study the cultural acculturation of the shophouse in one of the famous Chinatowns in Indonesia, Pecinan Glodok, in the visual form of facades and spatial organization. This research uses a historical approach by analyzing the reconstruction of events in the past based on historical facts. The study’s results reveal the cultural acculturation in the visual form of the facade and the organization of the Pecinan Glodok shophouse from Dutch, Chinese, and Betawi cultures on each building element.